A historical record of land cover change of the lesser prairie-chicken range in Kansas - Spencer, David A. (Kansas State University, 2014)
The Lesser Prairie-Chicken (Tympanuchus pallidicinctus) is a prairie grouse of conservation concern in the Southern Great Plains. In response to declining population numbers and ongoing threats to its habitat, the Lesser Prairie-Chicken was listed as threatened under the Endangered Species Act in May 2014. In western Kansas, the Lesser Prairie-Chicken occupies the Sand Sagebrush Prairie, Mixed-grass Prairie, and Short-grass/CRP Mosaic Ecoregions. Since the beginning of the 20th century, the overall range and population has declined by 92% and 97% respectively. Much of this decline is attributed to the loss and fragmentation of native grasslands throughout the Lesser Prairie-Chicken range. Whereas much of the loss and degradation of native grassland have been attributed to anthropogenic activities such as conversion of grassland to cropland and energy exploration, federal legislation since the 1980s to convert cropland on highly erodible soils to perennial grasses through the U.S. Department of Agriculture (USDA) Conservation Reserve Program (CRP) may curtail or reverse these trends. My objective was to document changes in the areal extent and connectivity of grasslands in the identified Lesser Prairie-Chicken range in Kansas from the 1950s to 2013 using remotely sensed data. I hypothesized that the total amount of grassland decreased between the 1950’s and 2013 because of an increase in agricultural practices, but predicted an increase of grassland between 1985 and 2013 in response to the CRP. To document changes in grassland, land cover maps were generated through spectral classification of LANDSAT images and visual analysis of aerial photographs from the Army Map Service and USDA Farm Service Agency. Landscape composition and configuration were assessed using FRAGSTATS to compute a variety of landscape metrics measuring changes in the amount of grassland present as well as changes in the size and configuration of grassland patches. Since 1985, the amount of grassland in the Lesser Prairie-Chicken range in Kansas has increased by 210,9963.3 ha, a rise of 11.9%, while the mean patch size and area-weighted mean patch size of grassland increased 18.2% and 23.0% respectively, indicating grassland has become more connected during this time in response to the CRP. Prior to the implementation of CRP, the amount of grassland had been decreasing since 1950, as 66,722.0 ha of grassland was converted to croplands. The loss of grassland had a considerable effect on the patch size of grasslands, as mean patch size and area-weighted mean patch size decreased by 8.8% and 11.1% respectively. The primary driver of grassland loss between 1950 and 1985 was the emergence of center pivot irrigation, which had its greatest impact in western and southwestern parts of the range in Kansas. In particular, while the amount of grassland in Range 5, a region of the Lesser Prairie-Chicken range found in southwest Kansas, has increased overall since the 1950s by 4.7%, the area-weighted mean patch size has decreased by 53.0% in response to center pivot irrigation fragmenting the landscape. While the CRP has been successful in increasing and connecting grassland throughout the Lesser Prairie-Chicken range to offset the loss of grassland since the 1950s, continuation of the CRP faces an uncertain future in the face of rising commodity prices, energy development, and reduction in program scope leaving open the possibility that these areas that have created habitat for Lesser Prairie-Chickens could be lost. As time progresses, a reduction in the scope of the CRP would reduce the amount of habitat available to Lesser Prairie-Chickens, threatening the persistence of their population.
Keywords: Lesser Prairie-Chicken; Conservation biology; Habitat; Remote sensing; Landscape ecology; Spatial analysis; Conservation Biology (0408); Environmental Sciences (0768); Wildlife Conservation (0284)